Antioxidant enzyme activities in anoestrus buffalo heifers supplemented with vitamin E and selenium - NAYYAR, SHASHI; GILL, VARINDER; SINGHA, S P S; SINGH, NARINDER; ROY, K S; SINGH, RAJVIR (The Indian Journal of Animal Reproduction, 2023)
The fifteen anoestrus buffalo heifers were divided into three groups viz. Group-I (control); Group-II-supplemented orally with 3500 IU vitamin E i .e. cx-tocopherol acetate per week per animal and Group-III-supplemented orally with cx tocopherol acetate +14 mg selenium as sodium selenite per week per animal; for two months. Supplementation of vitamin E alone increased erythrocytic glutathione peroxidase activity but decreased the level of lipid peroxidation and the activities of superoxide dismutase and glucose-6-phosphate dehydrogenase. Supplementation of selenium along with vitamin E resulted in the similar changes but the effect was slightly higher on the level of lipid peroxidation and glutathione peroxidase activity. The data indicates that selenium synergises the action of vitamin E in improving the antioxidant status as well as reproductive performance.